KONSEP NASIONALISME MENURUT ABDUL RAHMAN BASWEDAN - , FARIDAH ([Yogyakarta] : Universitas Gadjah Mada, 2014)
These studies attempting to explain this concept of nationalism in political philosophy and reveals about the concept of nationalism, abdul rahman baswedan the implementation of the concept of nationalism, abdul rahman baswedan against nationalism indonesia.Thinking about the concept of nationalism, abdul rahman baswedan very useful to raise its unity and integrity. This study is a research library. Primary literature used is a book by Abdul Rahman Baswedan entitled Some Notes on Indonesian Youth Pledge Arab Descent. This study uses philosophical hermeneutics analysis of New Media Elements: interpretation, description, holistika of reflection. Results obtained from this study are, first, the main points of thought Abdul Rahman Baswedan, namely anti-colonial, anti-discrimination, as well as the belief that the homeland is Indonesian of Arab descent. Secondly, nationalism in Political Philosophy related to the discussion of nationalism and independence, because nationalism can not be separated from the term nation. Between nationalism and nation is a socio-political phenomenon. Third, the concept of nationalism Abdul Rahman Baswedan reflected Kartodirdjo Sartono thinking, namely unity, liberty, equality, personality, and performance. On the other nationalism Abdul Rahman is based on the principle of ius soli Baswedan, which is where he was born, in that place is the motherland. Fourth, implementation of the concept of nationalism Abdul Rahman Baswedan against Indonesian nationalism, namely awareness of the Indonesian national unity, and mutual awareness of the Indonesian nation in eliminating all forms of colonialism and oppression in Indonesia. Keywords: nationalism, nation, unity and integrity.